Effectiveness of Educational Intervention on Mental Health Literacy among School Teachers of Selected Schools of Dharan Municipality - Bhattarai, Tilarupa; Lama, Sami (Journal of Nursing Education of Nepal, 2023)
Mental Health Literacy (MHL) includes knowledge and beliefs about mental health and its  disorders to help in their recognition, management and prevention. The school teachers are  required to have adequate knowledge in these aspects of health and illnesses to make them  aware of it and to help those who are in need. The aim of study was to assess the change  in knowledge and attitude after educational intervention among school teachers regarding  MHL. One group pre-test post-test research design was used in 4 schools of Dharan with  randomly selected 56 teachers. Data was collected in two phases using self-administered semi  structured questionnaire before and after the educational intervention. The data was analyzed  with descriptive and inferential statistics. The study findings revealed that median MHL score  increased from 111 to 128 after the intervention which was statistically significant (P=
Keywords: Mental Health Literacy; School Teacher; Effectiveness; Educational Intervention